FURTHER IMPROVEMENT OF MORTGAGE LOANS OFFERED TO THE POPULATION - Nurmukhamedov Bobir Botirovich (Scholar Express Journals, 2022)
In this article, in recent years, in order to raise the standard of living of the population in our country, to create sufficient conditions for a peaceful and prosperous life, in particular, to provide long-term mortgage loans in order to further improve the system of providing the population with affordable and highquality housing. the ongoing reforms are discussed.
Keywords: Mortgage loan; subsidy; diversification; social rent system